Crop Productivity and Nutrient Dynamics in a Shrub‐Based Farming System of the Sahel. (1st July 2013) - Dossa, Ekwe L.; Diedhiou, Ibrahima; Khouma, Mamadou; Sene, Modou; Badiane, Aminata N.; Ndiaye Samba, Samba A.; Assigbetse, Komi B.; Sall, Saidou; Lufafa, Abel; Kizito, Fred; Dick, Richard P.; Saxena, Jyotisna
Abstract : Piliostigma reticulatum (DC.) Hochst., an indigenous shrub, forms an important vegetative component of parkland cropping systems in the Sahel; however, its biophysical interactions with soil and crops are not well understood. Therefore, the objectives were to determine the impact of P. reticulatum, under varying fertilizer rates, on crop yield response and soil nutrient dynamics. The experiment had a split‐plot factorial design, where the main plot was shrub (presence or absence) and the subplot was fertilizer rate (0, 0.5, 1.0, or 1.5 times the recommended N–P–K fertilizer rate) applied to a peanut ( Arachis hypogaea L.)–pearl millet [ Pennisetum glaucum (L.) R. Br.] rotation. In 3 of the 4 yr, P. reticulatum improved or had no effect on crop yields when averaged across fertilizer rates. Overall, millet and peanut biomass and N and P uptake by millet increased in the presence of shrubs and with increasing fertilizer rate. Contrary to P, inorganic N in the soils changed very rapidly, reaching very low levels by the end of the growing season. The N content of soil leachates below the rooting zone was generally lower beneath than outside the shrub canopy, suggesting that the shrub conserves N that is otherwise lost through leaching. Piliostigma reticulatum increased particulate organic matter, indicating that this shrub improved soil quality. These results suggest that P. reticulatum, under nonthermal management and a higher density than typically found in farmers' fields, has ecological benefits with improved soils and reduced loss of N, which has implications throughout the Sahel.